The Level of Dialogue Skills for Tenth and Eleventh-Grade Students in Al-Batinah North Governorate Schools in the Sultanate of Oman from Their Perspective - Al-Jahwari, Mohammed Salim Ali; Al-Jammoussi, Jawhar AbdulQadir (Journal of Educational and Psychological Sciences, 2024)
This study aimed to investigate the dialogue skills of tenth and eleventh-grade students in the Al-Batinha North Governorate Schools in the Sultanate of Oman from the perspective, and identify the statistical differences attributed to gender and grade. The researcher adopted the descriptive survey approach and made questionaries of (24 phrases) under two fields; i.e. dialogue organization and dialogue practice. The study sample included (400) students of both genders. The study showed a high grade of the general average of students’ dialogue skills (3.73). The dialogue organization showed the first rank with an average of (3.90) followed by the dialogue practice with an average of (3.56). The results showed no statistically significant difference at the significance level of (α≤0.05) for the sample response concerning the level of dialogue skills attributed to (gender, grade). The researcher recommended increasing the level of participation and cooperation between the administration and school associates, arranging training events and activities to hone students’ dialogue skills, and making use of technology and artificial intelligence to enhance dialogue construction.